Identification of weaver ant behavior patterns (oechophylla smaragdina) - Zulfa, Putri Indana; Azzahra, Aulia Faradina Dwi Nabila; Muta'allimah, Muta'allimah; Nafi'ah, Nikmah Ilmin; Hayya, Adieba Warda (JPBIO (Jurnal Pendidikan Biologi), 2025)
Ants are insects that are widely distributed on land throughout the world and are known as eusocial insects that live in colonies and are very dependent on the presence of trees. This study aims to determine the behavior of weaver ants that are seen using the Ad-libitum Sampling method, to determine the behavior of weaver ants and their frequency using the Scan Sampling method, and to determine interesting weaver ant behavior patterns using the Behavior Sampling method. Observations of weaver ant behavior were carried out at PPST Bahjaturroghibin for a period of two months between October - November 2024. From the results of the observations, it was found that the behavior of weaver ants that were observed was moving activities with a percentage of 57%, looking for food with a percentage of 10%, grooming or cleaning themselves with a percentage of 5%, resting with a percentage of 7%, defense or horse stance before fighting with a percentage of 4%, fighting with a percentage of 4%, communication between ants with a percentage of 9%, and eating with a percentage of 4%. The most frequently observed activity is the activity of moving from one place to another.